Antioxidant and Nephroprotective Effects of Okra Pods Extract (Abelmoschus esculentus L.) against Lead Acetate-Induced Toxicity in Mice. (31st March 2020) - Wahyuningsih, Sri Puji Astuti; Savira, Nadyatul Ilma Indah; Anggraini, Devinta Wahyu; Winarni, Dwi; Suhargo, Listijani; Kusuma, Baskara Wiku Adi; Nindyasari, Faradita; Setianingsih, Nur; Mwendolwa, Adamu Ayubu
Abstract : In this study, we determine the curative effects of okra pods ( Abelmoschus esculentus L.) extract against lead acetate toxicity in mice kidney. n -Hexane, ethyl acetate, and methanol solvent were used for extracting okra pods. The role of the extract as an antioxidant was tested by DPPH and FRAP methods. The methanol extract was used for experiments in animals. A total of 30 male BALB/c mice were randomly divided into six equal groups: normal control, negative control (lead-induced), and treatment groups (lead-induced for 28 days and administration of methanol extract at doses of 50, 100, 200, and 400 mg/kg BW for the 28 days). The following were analyzed in all groups: activity of the antioxidant enzymes, namely, superoxide dismutase (SOD) and catalase (CAT); oxidant level, namely, malondialdehyde (MDA) and nitric oxide (NO); and markers of kidney injury, namely, blood urea nitrogen (BUN) and creatinine (Cre). Kidney histopathology was also evaluated. This study showed that the methanol extract showed the highest antioxidant activity (IC50 is 35.21  µ g/mL, and FRAP is 57.58  µ M Fe 2+/ g). The CAT and SOD activities increased significantly in okra-treated groups (P < 0.05 ). The okra administration groups experienced a significant decrease in MDA, NO, BUN, and Cre levels (P < 0.05 ). Thickness of the epithelial proximal tubule, diameter of the proximal tubule, and percentage of necrotic cells in proximal tubule decreased, but the diameter ratio of glomerular Bowman's capsule in mice treated with okra was optimally improved and repaired like normal control (P < 0.05 ). The results of this study reveal that methanol extract has a very strong antioxidant effect and can reduce the influence of toxicity induced by lead acetate in mice kidney.